Exergoeconomic analysis of solar absorption-subcooled compression hybrid cooling system. (15th July 2017) - Li, Zeyu; Liu, Liming; Jing, Yue
Highlights: Exergoeconomic model of hybrid system was developed. Greater size of absorption subsystem is suggested to the cost effective design. Tradeoff between investment and exergy destruction is in cooling set and compressor. Product cost flow rate in the optimal design comes down by 11.58%. Abstract: The solar absorption-subcooled compression hybrid cooling system is a novel and better solution for the building with many floors. The existing study only reports the thermodynamic study of solar absorption-subcooled compression hybrid cooling system but does not refer to the cost effective design of system. Hence, the paper mainly deals with the exergoeconomic investigation of solar absorption-subcooled compression hybrid cooling system and aims to present the design guideline of system. The exergoeconomic model of solar absorption-subcooled compression hybrid cooling system was developed at first. Subsequently, the corresponding analysis was performed and the effect of primary design parameter on the product cost flow rate was obtained and discussed. Finally, the global optimal design of system was carried out by the nonlinear direct search method. The result showed that the cost effective design of system mainly depends on the reasonable design of cooling capacity of absorption subsystem as well as component in the compression subsystem, i.e., condenser, evaporator and compressor. Besides, it was found that the trade-off between the investment cost and exergy destruction should be considered in the above-mentioned design. Compared to the base case, the product cost flow rate in the optimal design comes down by 11.58%. The paper is helpful to improve the design of solar absorption-subcooled compression hybrid cooling system and make system cost effective.